Spontaneous pneumothorax in a child with miliary tuberculosis: a case report - Muhammad Ali Shodikin; Dini Agustina (Indonesian Pediatric Society, 2022)
Spontaneous pneumothorax is a rare but fatal complication of miliary tuberculosis. We report a 13-year-old boy presenting with shortness of breath. He was diagnosed with miliary tuberculosis with spontaneous pneumothorax, which showed significant improvement after the insertion of a thoracostomy tube and anti-tuberculosis drug therapy.